Психологічний аналіз базових переконань у військовослужбовців - Коваленко, Є. С.; Kovalenko, Ye. S. (Дніпровський науковий часопис публічного управління, психології, права. - 2023. - № 1. - С. 193-197, 2023)
Досліджено базові переконання у військовослужбовців з ненормативною та умовно нормативною поведінкою. Доведено, що у військовослужбовці з умовно нормативною поведінкою мають відносно збіднені погляди щодо справедливості світу та можливостей контролювати події, водночас у них виявлено більш широкий світогляд щодо уявлень про прихильність та відчуття контрольованості ситуації. У військовослужбовців з ненормативною поведінкою визначена жвава динаміка показників базових переконань в контексті поглиблення уявлень щодо справедливості й контрольованості світу та ціннісного значення власного «Я». Наявність ненормативної поведінки в особистісному досвіді суттєво позначається на особливостях смислової сфери військовослужбовців першої групи, які мають дисциплінарні проступки.

The article presents a theoretical analysis of basic beliefs in psychological sources and an empirical study of the outlined phenomenon on a sample of military personnel. Theoretical studies have shown that a significant number of works are devoted to the basic beliefs of military personnel, which reveal their key content and probable consequences for the personality and effectiveness of the service as a whole. The article provides a brief overview of the specifics of military culture: norms, values, and behavioral characteristics. The normativity of behavior is an important factor in the legal behavior and culture of military personnel, forming legal intolerance to cases of injustice. The purpose of the work is an empirical study of the basic beliefs of servicemen with non-normative and conditionally normative behavior. 200 servicemen acted as research subjects. The groups were formed according to the indicator of their committing a disciplinary offense. The first group is servicemen with irregular behavior (having disciplinary violations), numbering 98 people. The second group is a control group, it included 102 servicemen with conditionally normative behavior. The survey was conducted in January-February 2022. To achieve the set goal and perform the empirical task was used the "Methodology of diagnosis of basic beliefs" by R. Janoff-Bulman. It has been empirically proven that military personnel with conditionally normative behavior have relatively impoverished views on the justice of the world and the ability to control events, while at the same time, they have a broader worldview on ideas about commitment and a sense of controllability of the situation. In servicemen with non-normative behavior, a lively dynamics of indicators of basic beliefs was determined in the context of deepening ideas about the justice and controllability of the world and the value of one's own "Self". That is, the presence of non-normative behavior in personal experience significantly affects the features of the semantic field of servicemen of the first group who have disciplinary offenses.

Исследованы базовые убеждения у военнослужащих с ненормативным и условно нормативным поведением. Доказано, что военнослужащие с условно нормативным поведением имеют относительно обедненные взгляды на справедливость мира и возможности контролировать события, в то же время у них выявлено более широкое мировоззрение относительно представлений о приверженности и ощущению контролируемости ситуации. У военнослужащих с ненормативным поведением определена оживленная динамика показателей базовых убеждений в контексте углубления представлений о справедливости и контролируемости мира и ценностном значении собственного «Я». Наличие ненормативного поведения в личностном опыте существенно сказывается на особенностях смысловой сферы военнослужащих первой группы, обладающих дисциплинарными проступками.
Psychological analysis of basic beliefs of military officers
Коваленко, Є. С. Психологічний аналіз базових переконань у військовослужбовців / Коваленко Євгеній Сергійович // Дніпровський науковий часопис публічного управління, психології, права. - 2023. - № 1. - С. 193-197. - DOI: https://doi.org/10.51547/ppp.dp.ua/2023.1.33.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; базові переконання; basic beliefs; базовые убеждения; військовослужбовці; military personnel; военнослужащие; дисциплінарні проступки; disciplinary offenses; дисциплинарные проступки; ненормативна поведінка; abnormal behavior; ненормативное поведение; правова інтолерантність; legal intolerance; правовая интолерантность; умовно нормативна поведінка; conditionally normative behavior